2019
DOI: 10.1371/journal.pone.0212010
|View full text |Cite
|
Sign up to set email alerts
|

Associations between alteration in plant phenology and hay fever prevalence among US adults: Implication for changing climate

Abstract: Plant phenology (e.g. timing of spring green-up, flowering) is among the most sensitive indicator of ecological response to ongoing climate variability and change. While previous studies have documented changes in the timing of spring green-up and flowering across different parts of the world, empirical evidence regarding how such ongoing ecological changes impact allergic disease burden at population level is lacking. Because earlier spring green-up may increase season length for tree pollen, we hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
16
0
4
Order By: Relevance
“…Human-caused climate change is expected to have widespread negative impacts on public health through a range of pathways ( 1 3 ). Climate change could trigger spatial and temporal shifts in plant airborne pollen loads, which have major respiratory health consequences for allergies and asthma ( 4 7 ), viral infections ( 8 ), school performance and downstream economic impacts ( 9 ), and emergency room visits ( 5 , 10 ). Because pollen concentrations are often highly temperature-sensitive ( 11 , 12 ), anthropogenic climate change could substantially harm respiratory health by increasing pollen concentrations and/or lengthening pollen seasons and exposure times ( 13 15 ).…”
mentioning
confidence: 99%
“…Human-caused climate change is expected to have widespread negative impacts on public health through a range of pathways ( 1 3 ). Climate change could trigger spatial and temporal shifts in plant airborne pollen loads, which have major respiratory health consequences for allergies and asthma ( 4 7 ), viral infections ( 8 ), school performance and downstream economic impacts ( 9 ), and emergency room visits ( 5 , 10 ). Because pollen concentrations are often highly temperature-sensitive ( 11 , 12 ), anthropogenic climate change could substantially harm respiratory health by increasing pollen concentrations and/or lengthening pollen seasons and exposure times ( 13 15 ).…”
mentioning
confidence: 99%
“…Sapkota et al . 58 did a US county assessment and showed that counties that experienced earlier spring onsets had a 14% increase in hay fever, indicating climate effects on changing plant phenology and the prevalence of AR. Overall, these studies are consistent with climate and/or CO 2 induced changes in aeroallergen production.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…Allergenic pollen levels are affected by climate, because warmer weather, higher humidity, and heightened levels of carbon dioxide in the atmosphere can stimulate the growth of certain plant species and can extend pollen production season (Neumann et al, 2018;Reid & Gamble, 2009;Sapkota et al, 2019;L. Ziska et al, 2011;L.…”
Section: Allergenic Oak Pollen In North Carolinamentioning
confidence: 99%
“…Allergenic pollen levels are affected by climate, because warmer weather, higher humidity, and heightened levels of carbon dioxide in the atmosphere can stimulate the growth of certain plant species and can extend pollen production season (Neumann et al, ; Reid & Gamble, ; Sapkota et al, ; L. Ziska et al, ; L. H. Ziska et al, ). Higher pollen levels from specific trees, grasses, and weeds are associated with asthma exacerbations (Sun et al, ).…”
Section: Data Sourcesmentioning
confidence: 99%